Should we apply “early” initiation of renal replacement therapy to critically ill patients with acute kidney injury? - Legrand, Matthieu (Journal of Thoracic Disease, 2016)
Renal replacement therapy (RRT) remained one of the cornerstones of treatment of severe acute kidney injury (AKI). Large randomized controlled trials had addressed the question of dosing of RRT in critically ill patients with AKI and failed to show an impact on mortality of high dosing using hemodiafiltration with standard membranes (1,2). With respect to strategy of RRT management in intensive care unit (ICU) patients the focus has now moved toward the question of timing of RRT in patients with AKI. Higher in-hospital mortality has been observed in retrospective cohort studies when RRT was applied lately in patients with AKI. Based on these findings and even though well-performed large scale randomized controlled trials were largely lacking, an early or preemptive used of RRT has been suggested to improve outcome in patients with AKI (3).